The impact of 5S on Microbiological Air Quality of an agrobiological products quality laboratory - Huánuco, Lucía (2018)
Microbiological air quality (MAQ) was monitored in the agrobiological products quality laboratory before and after the application of the "5S" methodology. The results were obtained through the agar-plate sedimentation method, carried out via biweekly sampling from April to June and from September to November of 2017, keeping temperature and relative humidity parameters constant (23 + 2 ° C and 62 + 3%). The initial level of 5S achieved only 43% of compliance, considered as "Below average", obtaining in this instance MAQ sampling distributed among fungi of 25 CFU/plate (50%), followed by bacteria at 16 CFU/plate (33%) and yeast at 8 CFU/plate (17%). In contrast, after carrying out 5S implementation, a result of 91% or "Excellent" level was obtained, which had fungal counts of 14 CFU/plate and 1 CFU/plate for the case of bacteria and yeasts. That is to say, the total microbial load decreased 68% between both conditions. By means of Student’s T test for means of related samples, significant differences in Microbiological Air Quality before and after 5S implementation at the laboratory studied were confirmed.